Analysis of the Readiness Level of Hospital Management Information System (HMIS) Security Based on the KAMI Index 5.0 at RS X 2026: Agni Dika Seutiani, Fery Fadly - Agni Dika Seutiani; Fery Fadly (STIKes Persada Husada Indonesia, 2026)
Research Objective: The Hospital Management Information System (SIMRS) improves the quality and efficiency of hospital services. However, incidents of health data leakage still pose risks to the security of patient information. A preliminary study at X General Hospital showed that SIMRS has been implemented in all service units. Nevertheless, an assessment of information security readiness has never been conducted, so potential risks to patient data have not been clearly measured. This study aims to determine the level of information security readiness of the Hospital Management Information System (SIMRS) using the KAMI Index 5.0. Methodology: This study used a quantitative descriptive design. Respondents were selected using purposive sampling. Data were collected through observation of security procedures, the KAMI Index 5.0 questionnaire, and supporting interviews. Data analysis was conducted by calculating scores for each assessment area and determining the readiness level using the readiness matrix of the KAMI Index 5.0. Results: The electronic system category obtained a score of 21, which falls within the range of 16–34, indicating a high level of dependence on electronic systems. The overall readiness score was 554, categorized as “Basic Framework Fulfillment,” indicating that security controls exist but are not consistently implemented. Conclusion: The hospital is still considered not ready because it has not reached the minimum score of 647 based on the KAMI Index 5.0. Therefore, improvements are needed, particularly in risk management, governance framework, and asset management to improve information security readiness.